(untitled) (Portuguese Journal of Family Medicine and General Practice, 2003)
Reflexion is a powerful learning tool. In General Practice, practice reflexion is particularly important due to the complexity of health problems faced and to the type of care provided. The author, in this article, develops the rational of critical incidents and explores their applicability in learning and teaching communication skills, during vocational training, as well their applicability in daily practice facing self continuing professional and personal development.